Niche overlap between Leptodactylus chaquensis (CEI 1950) and Leptodactylus podicipinus (COPE 1862), in an area in the municipality of Cuiabá, Mato Grosso - Martinez, Flavia Rodrigues; Ruete, José Pedro Forghieri (Seven Editora, 2023)
Amphibians are the first tetrapodes (gr. tetra, four + prunes, foot) vertebrates conquering the terrestrial environment, are important predators of insects and other invertebrates. Considered opportunistic with regard to feeding habits, and the diet of a given species may reflect in part the availability of prey in the habitat. The present work deals with the niche overlap between the species Leptodactylus chaquensis and Leptodactylus podicipinus based on field collections in the municipality of Cuiabá, Mato Grosso. DOI:https://doi.org/10.56238/alookdevelopv1-159